Prostate Cancer and Prostatic Diseases - Freedland, Stephen J.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
Prostate Cancer and Prostatic Diseases (PCAN) covers all aspects of prostatic diseases, in particular prostate cancer, the subject of intensive basic and clinical research world-wide. The journal also reports on exciting new developments being made in diagnosis, surgery, radiotherapy, drug discovery and medical management. PCAN is of interest to surgeons, oncologists and clinicians treating patients and to those involved in research into diseases of the prostate. The journal covers the three main areas - prostate cancer, male LUTS and prostatitis. PCAN publishes original research articles, reviews, topical comment and critical appraisals of scientific meetings and the latest books. The Editors and a distinguished Editorial Board ensure that submitted articles receive fast and efficient attention and are refereed to the highest possible scientific standard. A fast track system is available for topical articles of particular significance.
Keywords: Medicine; Cancer research; Biomedicine, general; Cancer Research